Book Review: Weaving a Realm, Vietnamese clothing from around 1500 AD - Roeland Paardekooper (EXARC Journal)
What a pleasure it was when this book landed on my coffee table! The book is bilingual Vietnamese – English, well designed and covers over 200 pages with hundreds of full-colour images. The book is a joint project by several Vietnamese from around the world who wished to add to the awareness of Vietnamese identities around the world. Viet Nam is so much more than what people remember of the Vietnam War. Even a quick peek into Wikipedia highlights the long standing culture of the country and its people.